Pengaruh Kebijakan Utang, Cash Holding dan Intellectual Capital terhadap Nilai Perusahaan - Aizul Fitri; Rakhmawati Oktavianna (AKUA: Jurnal Akuntansi dan Keuangan, 2024)
This study aims to identify and provide empirical evidence regarding the influence of debt policy, cash holding, and intellectual capital on firm value in consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange during the period of 2018-2022. The independent variables are Debt Policy, measured by the Debt to Equity Ratio (DER) index; Cash Holding, measured by the Cash Holding (CASH) index; and Intellectual Capital, measured by the Value Added Intellectual Coefficient (VAICTM) index, with the dependent variable being Firm Value, measured by the Price to Book Value (PBV). Utilizing a quantitative approach, this research draws on secondary data from annual reports on the Indonesia Stock Exchange, selecting 34 companies through purposive sampling. Descriptive statistical analysis was employed, and the data was processed using Eviews version 12. The results indicate that debt policy affects firm value, cash holding does not affect firm value, and intellectual capital affects firm value, while debt policy, cash holding, and intellectual capital collectively have a significant effect on firm value.